FRAUD TRIANGLE DAN FRAUD DIAMOND MODEL DALAM PREDIKSI KECURANGAN LAPORAN KEUANGAN - Fitri Hidayatun; Agung Juliarto (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the relevance of fraud triangle and diamond fraud models in predictions of fraudulent financial statements. The study uses two models, namely the fraud triangle and fraud diamond model where the triangle fraud model has three elements, namely pressure, opportunity and rationalization, whereas in the diamond fraud model there is a fourth element addition, namely ability. The population in this study are all companies listed on the Indonesia Stock Exchange in the period 201, while the sample in this research is Manufacturing Companies listed in the Indonesia Stock Exchange (BEI) periode 2017. The sample was selected using purposive sampling method and acquired 124 manufacturing companies which become the sample. This study uses quantitative method by using logistic regression analysis. The results of the study show that the diamond fraud model has a greater degree of conformity compared to the fraud trangle model, although the increase in significance is relatively very small. The results of statistical calculations show that the ability variables proxied by using changes in directors are less able to provide significant results because the changes in the calculation results are very small.